2006
DOI: 10.1007/s00170-006-0793-y
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of production workers’ performance variations and the potential impact of attitudes

Abstract: In most manufacturing systems the contribution of human labour remains a vital element that affects overall performance and output. Workers' individual performance is known to be a product of personal attitudes to work. However, in current system design processes worker performance variability is assumed to be largely insignificant and the potential impact of their attitudes is ignored. This paper describes a field study that investigated the extent to which workers' production task cycle times vary and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The managers are usually focused on factors as machinery, attendance and quality control, and professional knowledge and task training. However, previous research has definitely shown that there are other opportunities to optimize OLE; these consist of efforts aimed at optimizing environmental factors that affect the mental, social, and physical well-being of the workforce: workers’ attitudes and behaviours have a significant effect on their work performance and the production process [ 32 , 33 ]; and lack of motivation affects the labour effectiveness not only directly, but also indirectly through the workers’ knowledge and skills [ 30 ]. Production rate and labour effectiveness are also affected by health and safety of the labour force, ergonomic work conditions [ 9 , 10 ], ‘extrinsic rewards’ [ 29 ], and environmental factors such as noise, lighting, humidity, and temperature [ 7 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The managers are usually focused on factors as machinery, attendance and quality control, and professional knowledge and task training. However, previous research has definitely shown that there are other opportunities to optimize OLE; these consist of efforts aimed at optimizing environmental factors that affect the mental, social, and physical well-being of the workforce: workers’ attitudes and behaviours have a significant effect on their work performance and the production process [ 32 , 33 ]; and lack of motivation affects the labour effectiveness not only directly, but also indirectly through the workers’ knowledge and skills [ 30 ]. Production rate and labour effectiveness are also affected by health and safety of the labour force, ergonomic work conditions [ 9 , 10 ], ‘extrinsic rewards’ [ 29 ], and environmental factors such as noise, lighting, humidity, and temperature [ 7 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For all its returns, HSI cannot change the attitudes of workers. Furthermore, as concluded in [9] the attitude of the workers affects their performance to a higher degree than previously thought. These factor needs to be understood by the NPD team.…”
Section: Limitations and Areas For Future Studymentioning
confidence: 76%
“…Each one of these encompasses a wide array of uses, and the techniques may range from a basic method study model [7] to the newer models like PyraMAPs [2]. Most of these approaches have been used in order to accomplish one of the following: a) Study the human in relation with the system [9] [4][1] [17] b) Identify areas of volatility [2] [8] c) Attempt to reduce/remove these volatilities [7][11] [21] Human Systems Integration encompasses all the aforesaid fields and tries to bring about a single framework for humanrelated issues. It is uncommon to apply human factors to a product in its development phase [4] and wherever it has been done, the focus has been on reliability issues (or disasters occurring due to human factors) [16].…”
Section: Introductionmentioning
confidence: 99%
“…For instant, different workers' task performance varies due to gender (Beck et al, 2012) age (Ng and Feldman, 2008) and learning curve effect for same worker repeating a task (Globerson, 1980). Again without presenting the data, a study claimed that analysis of variance (ANOVA) and t-test procedures show little or no significant effect on workers' production task performance for differences between time-related conditions, namely: shift, week, day of the week, hour of day, hour in shift (Fletcher et al, 2008). Literature shows that a number of variables influence on the employee performances at work place in different production and service oriented organizations.…”
Section: Literature Reviewmentioning
confidence: 99%